Mid-Tudor Queenship and Memory: The Making and Re-making of Lady Jane Grey and Mary I. Edited by Valerie Schutte and Jessica S. Hower. Palgrave Macmillan, Basingstoke, 2023. ISBN 978-3-031-35688-9 (ebook) xi + 273 pp. £109.99 - Melita Thomas (Royal Studies Journal)
Mid-Tudor Queenship and Memory: The Making and Re-making of Lady Jane Grey and Mary I. Edited by Valerie Schutte and Jessica S. Hower. Palgrave Macmillan, Basingstoke, 2023. ISBN 978-3-031-35688-9 (ebook) xi + 273 pp. £109.99